Kohesi Gramatikal dalam Karangan Teks Eksposisi Siswa Kelas VIII SMP Negeri 16 Padang - Antika, Syafaria Esa; Emidar, Emidar (TSAQOFAH, 2023)
This type of research is a qualitative research with descriptive method. This research was conducted at SMP Negeri 16 Padang. The data of this study is the use of grammatical cohesion in expository text essays. The source of the data in this study was written exposition texts by class VIII students of SMP Negeri 16 Padang. Based on the results of research on the use of grammatical cohesion in exposition text essays for class VIII students of SMP Negeri 16 Padang, there is the use of grammatical cohesion, namely references, substitutions, ellipsis, and conjunctions. Based on the data analysis that has been done, the most dominant use of grammatical cohesion used in exposition texts for class VIII students of SMP Negeri 16 Padang is the use of conjunctions and the least use of grammatical cohesion found is the use of ellipsis. From the quantitative data, it can be categorized as an error in the use of grammatical cohesion in an exposition text essay for class VIII students of SMP Negeri 16 Padang, which is included in the high category.